Adenolipoleiomyoma Polyp of the Uterus: A Case Report and Review of the Literature - Xavier Catteau; Vincent Anaf; Jean-Christophe Noël (Case Reports in Pathology)
Adenolipoleiomyoma is a very rare lesion of the uterus. Only four cases were reported. We describe one case of adenolipoleiomyoma presenting as a polyp in a postmenopausal woman with menorrhagia. Adenolipoleiomyoma is a very rare lesion and the histogenesis remains unclear. We discuss the origin and the differential diagnosis of this lesion.